Measurement of Competitiveness and Determinants of Coal Output in East Kalimantan (International Journal of Scientific Research in Science and Technology, 2024)
The coal sector has the highest share and contribution to the economy in East Kalimantan Province. The importance of the existence of coal to the economy of East Kalimantan must be followed by high competitiveness and supportive policy direction. For this reason, this study aims to measure and identify the competitiveness and factors that affect the output of the coal sector in East Kalimantan Province using the competitiveness analysis (LQ) method and panel data regression. The results of the analysis identified that East Kalimantan occupies the first position with the highest coal sector competitiveness in Indonesia. This is evidenced by a consistent competitiveness index value of more than 1 from 2021 to 2024. Meanwhile, the results of the panel data analysis also identified that the variables of total investment and the number of workers in the coal sector with long roads are estimated to have a positive and significant effect on the output of the coal sector in East Kalimantan Province. Meanwhile, the road length variable is predicted to have a negative and significant effect on the output of the coal sector.